FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI SAWAH (Oryza sativa L.) DI DESA BINALAWAN KECAMATAN SEBATIK BARAT KABUPATEN NUNUKAN (Factors Influencing Production of Wetland Paddy (Oryza sativa L.) in Binalawan Village West Sebatik Subdistrict Nunukan District) - ASHAR ASHAR; SITI BALKIS (Universitas Mulawarman (University of Mulawarman), 2018)
Inputs are the absolute requirement in the process of production, if the one of production factor is not fulfilled then the process of production will not running smoothly in other words will not maximize. The purposes of this study were to know the influence of land size, capital, and labor to the production of wetland paddy in Binalawan Village West Sebatik Subdistrict. This study was held from September to November 2017. Sampling method in this study was simple random sampling with total of 32 farmers as respondents. Data analysis used multiple linear regression. The result of t test showed that the land size, capital, and labor do not influence the decrease of wetland paddy production, it was showed from the value of tcount (1.518) < ttable (2.048). The land size, capital, and labor influence the production of wetland paddy, this was showed from the value of Fcount (3.557) > Ftable (2.930). R shows that there are relation between land size, capital, and labor to the production of wetland paddy, Rcount (0.526) with significant value was 0.026 shows there are relation or middle correlation between land size, caapital, and labor to the production of wetland paddy in Binalawan Village.